(untitled) (Research, Society and Development, 2022)
The COVID-19 (2019-nCoV) pandemic caused many impacts on the population, due to the need for social isolation. In this case, elderly people who are part of the risk group felt this distance even more rigidly, especially those who live in Long Stay Institutions for the Elderly - ILPI. There is a lot of talk about distractions to meet this need for contact with affective bonds, as music is a way of entertainment and also of remembrance of memories of the past, we think about how the act of listening to music may have been an ally in this pandemic moment. For the constitution of the information, the theoretical and methodological assumptions of the participant research were used with a qualitative approach carried out through interviews and a live program with a repertoire of old songs for the elderly living in the house. Aiming to investigate how musical memories can contribute to overcoming social isolation in an ILPI. In this way, we can conclude that during the research, it was possible to observe that a moment of musical songs contributed to a mix of joy and remembrance among the residents of the Long Stay Institution - Casa da Fraternidade. However, we consider that it is not only necessary to encourage new policies that contemplate the guarantee of these elderly people, but also to investigate the well-being and experience of these subjects.